Formação de professores de dança: um estudo da etnocenologia a partir das narrativas dos egressos da Licenciatura em Dança do PARFOR/ETDUFPA - PEREIRA, Ricardo Augusto Gomes (Universidade Federal do Pará, 2019)
This thesis studies the training of the teacher of Dance, which constitutes the object of analysis from the categories "popular culture" and "Ethnoscenology", in the context of the Basic Education Teacher Training Program (Programa de Formação de Professores da Educação Básica – PARFOR), conducted by the School of Theater and Dance of the Federal University of Pará (Escola de Teatro e Dança da Universidad Federal do Pará – ETDUFPA), in the course of Graduation in Dance, between 2011 and 2018. Problematizes the said themes in the conduction of the course, whose graduates are the subjects of the research. It aims to analyze the evidences of popular culture and Ethnoscenology in the narratives of the graduates of the course of Graduation in Dance. To achieve this, it attaches itself to ethnomethodology and narrative analysis, which was made possible through conversations to identify what goes through the lines and the meanings that the subjects attribute to the teacher training, popular culture and Ethnoscenology. The results show that the training of the Dance teacher in PARFOR has improved 81 teachers in five municipalities (Castanhal, Capanema, Santarém, Marabá, Mãe do Rio), and that the reflexes of this training began to take effect, since, despite not having the objective conditions for the teaching of Arts in the language of Dance, the process experienced during the course influenced the work of the teachers, which has in Ethnoscenology an important entity, since it is associated with popular culture in school activities through work with the body and with the movement in the artistic and pedagogical perspective. Through the narratives of the former students of the Graduation in Dance, concludes that the formation of the dance teacher has evidenced Ethnoscenology and popular culture through the work of the graduates in the schools; however, this is not theoretically reflected in the speech of these subjects. Regarding the use of the narratives, it considers that they were revealing in terms of the pedagogical work that these professionals have been carrying out in the schools in the interior of Pará.